IoT-based Landsat 9 Satellite Tracking System - Ismail, Muhammad Adib; Homam, Mariyam Jamilah (Evolution in Electrical and Electronic Engineering, 2023)
In today’s world, the growth of Internet of Things (IoT) applications in our everyday lives increases. Smart devices, sensor technologies, and the internet enable seamless data gathering, communication, and processing across a variety of applications in the digital and physical worlds. The aim is to track the location of Landsat 9 satellite and get the captured images from the satellite and view in IoT application. Blynk. The satellite tracking system links with an ESP32 microcontroller to deliver data to Blynk for additional cloud-based services and data analysis. Two-Line Element (TLE) data is given to any Earth-orbiting objects and a model called Simplified General Perturbations 4 (SGP4) is used with TLE data to predict and simulate the satellite position at any given point in time. From the results, since the orbital inclination and height of the Landsat 9 satellite are approximately 98.2° and 705 km, respectively, the maximum values of the latitude and altitude are slightly above 80° and less than 720 km, respectively. The images captured by the satellite show the changes of the Earth’s land over time. The proposed system operates effectively in a setting with constrained resources and is lightweight and can be used anywhere.